Wills written by bilinguals in the Jauja Valley (Peru, 17th century) - Kolbinger, Ulrike (2012)
This article aims to analyse, from a discourse-pragmatic point of view, testaments of the Jauja Valley (central Peru) during the 17th Century, which are seen as manifestations of the linguistic and textual knowledge of their writers. In these testaments can be found linguistic and textual phenomena, which represent results of the Spanish-Quechua language contact. Therefore, it can be concluded that the analysed testaments were written by indigenous writers. The purpose of the article is to contribute to the investigation of the role of indigenous writers in the 17th Century in the central Andes of Peru.